Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1002/brb3.1553
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of right‐to‐left shunt in the different subgroups of migraine

Abstract: Objective Several investigations have documented an association between migraine and right‐to‐left shunt (RLS). However, whether there are specific clinical features that can distinguish between migraine patients with and without RLS is unclear. This study aims to explore whether there are specific clinical features that can distinguish between migraine patients with and without RLS, and to investigate the relationship between the degree of shunt and clinical parameters of headache. Methods In this study, we e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
0
5
1
Order By: Relevance
“…Some studies have found that RLS grades are related to the severity of migraine [ 28 ], but our study did not find a correlation between RLS and HIT-6 scores. The possible reason may be that the sample size of our study is small.…”
Section: Discussioncontrasting
confidence: 99%
“…Some studies have found that RLS grades are related to the severity of migraine [ 28 ], but our study did not find a correlation between RLS and HIT-6 scores. The possible reason may be that the sample size of our study is small.…”
Section: Discussioncontrasting
confidence: 99%
“…Beside, the blood flow velocity of the middle cerebral artery is also suggested to be correlated with the development and prognosis of migraine. Therefore, the detection and analysis of intracranial hemodynamics in patients with migraine is the main concern of many researchers ( 46 , 48 51 ). Given the importance of hemodynamic changes in migraine and the usefulness of their detection for the diagnosis and evaluation of this condition, changes in blood flow velocity detected by TCD were analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…35 Migraine is characterised by a left-right distribution of pain, and there are also left-right differences in its pathogenesis. Some studies have shown left-right vascular shunting in migraine, 36 left-right asymmetries in substances involved in pain, such as dimethylarginine, 37 and differences in the left-right functional response of the central hemisphere. 38 Whether there is modulation of the central brain mechanisms around acupuncture for migraine has not been confirmed by studies, but as a verification of the efficacy of CAT, migraine is certainly a good vehicle for the disease.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%